2018
DOI: 10.1016/j.ijdevneu.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of fetal toxicity relevant to sevoflurane exposures during pregnancy

Abstract: Over the last three decades, advances in medical and surgical techniques have proven life saving and life‐improving for young children. Consequently, early and repeated exposure to general anesthetics in childhood has increased. However, accumulating evidence suggests that general anesthetics may be neurotoxic in children. Of particular concern is the neurotoxicity fetuses may suffer from maternal exposure to sevoflurane during surgeries and fetal intervention procedures performed during the second trimester, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 90 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…In agreement with these previous studies, this study demonstrated that sevoflurane exposure during early pregnancy in rats damages the neuronal growth of the offspring by affecting the NR4A1/ Most general anesthetics are lipophilic and easily cross the placenta, and neurogenesis, neuronal migration, and corticogenesis are major neurodevelopmental events in early and middle pregnancy [29], which may explain why the neurotoxic effect of anesthesia on the brain development of offspring is greater in early gestation than in late gestation. The long-term neuroinflammatory effect of sevoflurane may be mediated by the release of inflammatory mediators, which would further aggravate the oxidative stress response [20]. These mediators of neuroinflammation could induce neurobehavioral dysfunction, and cause cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with these previous studies, this study demonstrated that sevoflurane exposure during early pregnancy in rats damages the neuronal growth of the offspring by affecting the NR4A1/ Most general anesthetics are lipophilic and easily cross the placenta, and neurogenesis, neuronal migration, and corticogenesis are major neurodevelopmental events in early and middle pregnancy [29], which may explain why the neurotoxic effect of anesthesia on the brain development of offspring is greater in early gestation than in late gestation. The long-term neuroinflammatory effect of sevoflurane may be mediated by the release of inflammatory mediators, which would further aggravate the oxidative stress response [20]. These mediators of neuroinflammation could induce neurobehavioral dysfunction, and cause cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms are involved in neuronal damage to offspring, for example neuronal apoptosis [ 16 ], synaptic plasticity [ 17 ], and BDNF-related pathways [ 18 , 19 ]. Chai et al [ 20 ] reviewed the fundamentals of fetal toxicity related to gestational sevoflurane exposure and demonstrated that the pathology associated with fetal toxicity involves oxidative stress, neuroinflammation, neuronal apoptosis, and alteration of synaptic properties. However, existing studies have mainly focused on the effects of sevoflurane exposure in a single stage of pregnancy [ 16 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on its inhibition of uterine contraction, which can prevent premature delivery, sevoflurane is the most widely used inhalation anesthetic during pregnancy. Sevoflurane easily impacts fetuses though the placenta [30]. Zheng et al [9] found that with the inhalation of 2.5% sevoflurane for 2 hours and 4.1% sevoflurane for 6 hours, the offspring of pregnant rat showed decreased learning and memory ability, accompanied by the release of inflammatory agents in the hippocampus and abnormal synaptic development.…”
Section: Discussionmentioning
confidence: 99%
“…Judging by animal model studies (reviewed in ref. 89 ), exposure to sevoflurane during uterine quiescence can induce neuroinflammation, neuroapoptosis, and eventually memory impairment. Cognitive impairment was also reported in young mice repeatedly exposed to sevoflurane, which caused an increase in proinflammatory proteins IL-6 and TNF-α ( 73 ).…”
Section: Inhalational (Volatile) Anaestheticsmentioning
confidence: 99%